Prospective, randomised trial of the time dependent antiplatelet effects of 500 mg and 250 mg acetylsalicylic acid i. v. and 300 mg p. o. in ACS (ACUTE) - Zeymer, Uwe; Hohlfeld, Thomas; Dahl, Jürgen vom; Erbel, Raimund; Münzel, Thomas; Zahn, Ralf; Roitenberg, Alexander; Breitenstein, Stefanie; Ferenc Pap, Ákos; Trenk, Dietmar (Thrombosis and Haemostasis, 2017)
Little is known about the onset of action after intravenous or oral administration of acetylsalicylic acid (ASA) in patients with acute coronary syndromes (ACS). The aim of the study was to compare intravenous 250 or 500 mg acetylsalicylic acid (ASA) with oral 300 mg in ASA naïve patients with ACS concerning the onset of antiplatelet effects measured by time dependent thromboxane inhibition. A total of 270 patients with ACS < 24 hours were randomised into one of three treatment arms comprising administration of a single dose of ASA as soon as possible after admission. The primary endpoint was platelet inhibition assessed by measurement of arachidonic acid (AA)-induced platelet thromboxane release (TXB2) 5 minutes (min) after study drug administration. Both 250 mg and 500 mg ASA i. v. inhibited TXB2 formation nearly completely (geometric means: from 581.7 and 573.9 ng/ml at baseline to 3.9 and 3.1 ng/ml at 5 min, respectively) compared to 300 mg oral ASA (geometric means: from 652.0 to 223.7 ng/ml) (p-value, ANCOVA: < 0.0001). Similar results were obtained for inhibition of AA-induced platelet aggregation (Multiplate ASPItest; from means 86.41 and 85.72 U to 23.04 and 20.57 U at 5 min, respectively) compared to 300 mg oral ASA from mean 87.18 to 75.56 U (p-value, ANCOVA: <0.0001). The rate of bleedings was low and comparable between the groups. In summary, the administration of a single dose of 250 or 500 mg ASA IV compared to 300 mg orally is associated with a faster and more complete inhibition of thromboxane generation and platelet aggregation. Bleeding complications were comparable between the groups.Supplementary Material including a list of institutions where work was performed is available online at www.thrombosis-online.com.
Keywords: Acute coronary syndrome; acetylsalicylic acid; platelet inhibition; thromboxane; intravenous